Changing leaf nitrogen and canopy height quantify processes leading to plant and butterfly diversity loss in agricultural landscapes. (3rd March 2014) - Hodgson, John G.; Tallowin, Jerry; Dennis, Roger L. H.; Thompson, Ken; Poschlod, Peter; Dhanoa, Mewa S.; Charles, Mike; Jones, Glynis; Wilson, Peter; Band, Stuart R.; Bogaard, Amy; Palmer, Carol; et al.
Summary We describe a novel method for quantifying ecosystem drivers that potentially compromise the effectiveness of agri‐environment schemes. We use three sources of data that for many countries are already in the public domain: governmental agricultural statistics, which provide a quantitative assessment of farming intensity in the 'working landscape', data on threat status and species distribution for plants and butterflies from conservation agencies and similar bodies and functional traits of plant species abstracted from published data bases. Changes in land use alter ecosystem processes which in turn modify both biodiversity and representation of functional types at the landscape scale. We interpret functional shifts to quantify important ecological drivers of floristic and faunal change and their causal land use origins. We illustrate the power of this approach by means of a worked example. We demonstrate that despite conservation policies to counteract them, eutrophication, identified by leaf nitrogen content, and abandonment, correlated with plant canopy height, are still causing biodiversity loss to native higher plants and butterflies in the English countryside. We use our analyses to suggest how conservation policies can be made more effective and discuss how similar approaches could be applied elsewhere.